2013
DOI: 10.1136/sextrans-2012-050801
|View full text |Cite
|
Sign up to set email alerts
|

Non-disclosure of HIV status in UK sexual health clinics—a pilot study to identify non-disclosure within a national unlinked anonymous seroprevalence survey

Abstract: Objectives To identify if HIV-infected individuals attending genitourinary clinics in the UK are not disclosing their HIV status, and to examine the potential utility of drug detection as a method to indicate nondisclosure. Methods HIV-positive samples from the unlinked anonymous seroprevalence survey from one London centre in 2009 had viral load (VL) assays performed to identify samples with VL below the level of detection (50 copies/ml, VLBLD) or <1000 copies/ml. After data matching, known HIV positives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…6 Although HIV testing is not usually performed for individuals with a prior HIV diagnosis, it may occur in clinical settings or clinical trials to confirm self-reported HIV status or to determine HIV status in individuals who are aware of their HIV infection but choose not to disclose this information. 79 …”
mentioning
confidence: 99%
“…6 Although HIV testing is not usually performed for individuals with a prior HIV diagnosis, it may occur in clinical settings or clinical trials to confirm self-reported HIV status or to determine HIV status in individuals who are aware of their HIV infection but choose not to disclose this information. 79 …”
mentioning
confidence: 99%
“…Population prevalence of HIV in the UK is estimated by data synthesis and statistical modelling 1. Multiple data sources include the GUM Anon survey that tests unlinked, anonymised residual samples of blood taken for routine syphilis testing from users of 16 genitourinary medicine (GUM) clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Concern has been expressed that the proportion of the undiagnosed HIV-infected population is inflated because some people with diagnosed HIV seek screening for sexually transmitted infections (STIs) at services away from their usual care provider without disclosing their HIV status 1 3. Research indicates that this may be the case but does not explain why.…”
Section: Introductionmentioning
confidence: 99%
“…We are reminded in this month's Editor's Choice by Lowndes et al 5 of continuing felt need for confidentiality in a report which for the first time estimates HIV non-disclosure by HIV diagnosed men in London STI clinics. Using an anonymous seroprevalence survey, the authors scrutinised HIV positive samples reported as undiagnosed, and found a substantial proportion of individuals to have a very low viral load, with antiretrovirals present.…”
mentioning
confidence: 99%